Outcomes of Joint Arthrodesis in Patients With Systemic Sclerosis - Melanie Bertolino, BS; Kyra A. Benavent, BS; Zachary Li, BS; Dafang Zhang, MD; Philip E. Blazar, MD; Brandon E. Earp, MD (Journal of Hand Surgery Global Online)
Purpose: Systemic sclerosis (scleroderma) is a chronic autoimmune connective tissue disorder that can lead to notable pain and functional limitations of the digits. This study assessed complications and reoperations after interphalangeal (IP) joint arthrodesis in patients with scleroderma. Methods: A retrospective review was performed of all patients who underwent digital joint arthrodesis of the proximal IP (PIP), distal IP, or thumb IP joints between September 1, 2006, and December 31, 2019, at an integrated health system comprising two level-I trauma centers and two community teaching hospitals. Six patients who underwent arthrodesis of 13 IP joints were included in the study. Patient demographics, comorbidities, surgical information, and postoperative outcomes were collected from the medical record. Results: Thirteen digits in six patients were treated with digital joint arthrodesis. Three patients had diffuse scleroderma, and four patients were women. The majority of procedures were performed on the PIP joint with Kirshner wires (nine of 13). No patients experienced intraoperative complications. Three patients experienced postoperative complications including flexion deformity, discomfort, and cellulitis. In patients who had primary arthrodesis, two of nine joints went on to nonunion. One patient who underwent arthrodesis of four PIP joints for failed PIP arthroplasties went on to nonunion of all four digits. Of the patients with complications and nonunion, three required reoperation. Conclusions: Our study suggests that arthrodesis is an acceptable treatment option for patients with joint deformities secondary to scleroderma; however, surgeons and patients should be aware of higher rates of complications. Type of study/level of evidence: Therapeutic III.